Pembuatan Modul Pembelajaran tentang Instalasi Komputer dan Telepon (Pabx) Di Sekolah Menengah Pertama Negeri 3 Purwodadi Grobogan Jawa Tengah - Rahmanto, Nurwahyu Septian Adi; , Moch. Muslich, S.T., M.Eng (2016)
Now the computer has become mandatory items that should be in every home or office , as well as a phone . Although there is now a laptop and mobile phone are more flexible and can be brought anywhere , but the computer and the phone can not be abandoned. Because the needs of each person is different . Therefore, the author tries to make learning module for Junior 's . This module is made to facilitate the students in learning and applying knowledge about computers and telephone installations . On this occasion the author will create a module for the installation of standard office computer or the home user and the type of PABX telephone . In this module the author only limits on the installation to be used alone , does not include the program and how to use it.